PENGARUH LINGKUNGAN KERJA, FLEKSIBILITAS JAM KERJA, WORK LIFE BALANCE TERHADAP PRODUKTIVITAS KARYAWAN - Rifda Rifda; Nur Asni Gani (Media Riset Bisnis Ekonomi Sains dan Terapan, 2026)
Previous studies on employee productivity have mainly focused on office and manufacturing sectors, with limited attention to Generation Z employees in the food and beverage industry. Generation Z tends to value a supportive work environment, flexible working hours, and work–life balance. In a shift-based food and beverage setting, these factors are expected to influence productivity.This study examines the effects of work environment, work schedule flexibility, and work–life balance on the productivity of Generation Z employees at Kopi Kenangan Area 2.9 using a quantitative approach with saturated sampling of 43 employees. Data were collected through questionnaires and analyzed using multiple linear regression.The results indicate that work environment and work–life balance have a positive direction of influence, while work schedule flexibility shows a negative direction. However, none of the variables significantly affect employee productivity, suggesting that productivity is more strongly shaped by operational demands and shift-based work systems.Keywords : Work Environment, Work Schedule Flexibility, Work–Life Balance, Employee Productivity, Generation Z